The relationship between food reeducation and physical activity in old age (Research, Society and Development, 2022)
The prolongation of age during life is accompanied by changes that result in a series of changes that can interfere with the nutritional, physical and functional status of the elderly. In view of this, the study aims to highlight the importance of the relationship between food reeducation aligned with the practice of physical activity as a way of improving the quality of life of the elderly. The methodology is a systematic literature review, based on obtaining data on research platforms such as Scielo, Google Scholar and Capes Periodical, in order to deepen scientific knowledge about the importance of healthy eating related to physical condition. The results achieved indicate that in the elderly, healthy eating habits and physical exercises are extremely important for the prevention and combat of various pathologies and, allow the reduction of functional losses, thus contributing to greater independence and favoring health conditions. In this way, it was possible to conclude that the change in the lifestyle of this part of the population must be disseminated and practiced, so that they can develop more health, disposition and longevity.